Design of a rhenium-decorated mesoporous nickel phyllosilicate-derived Ni–Re/MCM-41 catalyst for efficient hydrogenation of levulinic acid to γ-valerolactone - Yupawan Maneewong; Pratikkumar Lakhani; Sakhon Ratchahat; Chularat Sakdaronnarong; Wanwisa Limphirat; Bunyarat Rungtaweevoranit; Prof. Suttichai Assabumrungrat; Kanyanat Khosukwiwat; Kittisak Choojun; Tawan Sooknoi; Keiichi Tomishige; Atthapon Srifa (Green Chemistry, 2026)
The NiRe-PS catalyst achieves complete LA conversion with high GVL yield under mild conditions, exhibiting a high turnover frequency. Isotopic studies reveal dual hydrogenation pathways, highlighting enhanced catalytic efficiency and sustainability.
Keywords: Catalysis for Biomass Conversion; Layered Double Hydroxides Synthesis and Applications; Mesoporous Materials and Catalysis